2019
DOI: 10.3390/ijerph16101864
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diseases and Employment: Which Interventions Support the Maintenance of Work and Return to Work among Workers with Chronic Illnesses? A Systematic Review

Abstract: The increase of chronic diseases worldwide impact quality of life, cause economic and medical costs, and make it necessary to look for strategies and solutions that allow people with chronic diseases (PwCDs) to lead an active working life. As part of the CHRODIS Plus Joint European Action project, a systematic review was conducted to identify studies of interventions that support the maintenance of work and return to work (RTW) among workers with chronic illnesses. These interventions should target employees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 31 publications
4
73
0
5
Order By: Relevance
“…Concerning the relationships between RTW and the quality of working life (e.g., interpersonal relations, levels of social support), our results suggested that supervisor support is linked to job satisfaction [ 62 , 76 , 77 ] in the case of a disease. Despite this empirical evidence, the psychosocial meaning of support should be considered with caution.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Concerning the relationships between RTW and the quality of working life (e.g., interpersonal relations, levels of social support), our results suggested that supervisor support is linked to job satisfaction [ 62 , 76 , 77 ] in the case of a disease. Despite this empirical evidence, the psychosocial meaning of support should be considered with caution.…”
Section: Discussionmentioning
confidence: 87%
“…All were published in journals included in the Journal Citations Reports. Funding sources were specified, with some exceptions, such as the study carried out by Abegglen et al [ 62 ], which was supported by the Swiss Accident Insurance Fund. The origin of the sample was coded based on the information provided in the description of the samples, with the majority of the research conducted in the United States of America and Europe, while several studies were from Brazil or Japan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific evidence was studied by conducting systematic literature studies on best practices for assessing and promoting employees' wellbeing and health, preventing the development of chronic diseases, and fostering the work participation of employees with one or more chronic diseases [16][17][18][19]. Experiential data was collected through 45 interviews altogether, conducted with managers and employees from various industry sectors, as well as with occupational wellbeing and health professionals from six European countries.…”
Section: Methodsmentioning
confidence: 99%